Stair‐step particle flux spectra on the lunar surface: Evidence for nonmonotonic potentials?. Issue 1 (11th January 2017) - Collier, Michael R.; Newheart, Anastasia; Poppe, Andrew R.; Hills, H. Kent; Farrell, William M.
Abstract: We present examples of unusual "stair‐step" differential flux spectra observed by the Apollo 14 Suprathermal Ion Detector Experiment on the lunar dayside surface in Earth's magnetotail. These spectra exhibit a relatively constant differential flux below some cutoff energy and then drop off precipitously, by about an order of magnitude or more, at higher energies. We propose that these spectra result from photoions accelerated on the lunar dayside by nonmonotonic potentials (i.e.,  potentials that do not decay to zero monotonically) and present a model for the expected differential flux. The energy of the cutoff and the magnitude of the differential flux are related to the properties of the local space environment and are consistent with the observed flux spectra. If this interpretation is correct, these surface‐based ion observations provide a unique perspective that both complements and enhances the conclusions obtained by remote‐sensing orbiter observations on the Moon's exospheric and electrostatic properties. Key Points: SIDE has observed spectra on the lunar surface that reveal the presence of nonmonotonic potentials These are unique observations because SIDE makes them from the lunar surface rather than from orbit The spectra formed by nonmonotonic potentials reveal characteristics of the plasma environment including lunar surface potential